Modality matters: On social forces determining what is standard in German Sign Language (DGS) - Jaeger, Hanna (Linguistik Online, 2017)
Focusing on the social situation of German Sign Language (DGS) and their users, the article explores to what extent Ammon’s model of social forces that determine what is standard in language can also be applied to visual spatial languages. The paper demonstrates that Am-mon’s model is implicitly modality bound and as such cannot fully account for the situation of DGS-using community which largely consists of L2-signers. Although an alternative mod-el is not explicitly offered, the author shows that the model of social forces will need to be extended in order to be modality independent, i.e. applicable to both spoken and signed lan-guages and their communities.